I (5x - 8y = 9
II (2x + 3y = 16 (*-2.5)
Addition:
I (5x - 8y = 9
II (-5x -7.5y = -40
-----------------------
-15.5y = -31
y = -31 : -15.5
y = 2
So,
5x - 8y = 9
5x - 8(2) = 9
5x = 9 + 16
5x = 25
x = 25 : 5
x = 5
Solution: {There are x and y in R| x = 5 and y = 2}
><
2007-02-10 15:46:11
·
answer #1
·
answered by aeiou 7
·
0⤊
0⤋
5x-8y=9
2x+3y=16
Multiply 5 to (2x+3y=16)and 2 to (5x-8y=9).
This will give you:
10x-16y=18
10x+15y=80
Subtract.
-31y=-62
Which means y=2
Substitute y=2 into one of the original equations.
5x-16=9
Transpose.
5x=9+16.
5x=25.
x=5
And here's the final answer:
x=5 y=2
2007-02-10 16:01:56
·
answer #2
·
answered by FLY PIG FLY! 2
·
0⤊
0⤋
Multiply your bottom equation by 5 to get 10x +15y = 80
Multiply your top equation by 2 to get 10x -16x = 18
Subtract the first equation from the second
10x + 15y = 80
-(10x - 16y = 18)
= 0x + 31y = 62
therefore y = 2
Plug that into one of the original equations => 5x -8(2) =9 or 5x = 25 or x = 5
Double check it in the other original equation => 2(5) + 3(2) = 16, which is true, therefore x = 5 and y = 2
2007-02-10 15:52:51
·
answer #3
·
answered by billy b 3
·
0⤊
0⤋
5x - 8y = 9 multiply by 2
10x-16y=18
2x + 3y = 16 multiply by -5
-10x-15y=-80
10x-16y=18 add
-31y=-62 divide both sides by -31
y=2
2x + 3y = 16 substitute 2 for y
2x+3*2=16
2x+6=16 subtract 6 from each side
2x=10 divide both sides by 2
x=5
(5, 2)
check
5x - 8y = 9 substitute 5 for x & 2 for y
5*5-8*2=9
25-16=9
9=9
2007-02-10 16:27:07
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
x= 5 y=2
solve the first equation for x
5x=9+8y ----> x=(9+8y)/5
Now replace the x value in the second equation
2[(9+8y)/5] + 3y = 16 ----> (18+16y)/5 + 3y = 16
times 3y by 5/5 ----> 15y/5 and simplify
[18+(16y+15y)]/5 = 16 ---> (18+31y)/5 = 16
times both sides by 5
18+31y = 80 ---> 31y=62 y=2
Now take y and place the value in the equation that is easiest
2x+3(2)=16 ----> 2x+6=16 ---> 2x=10 ----> x=2
therefore x=5 and y=2
2007-02-10 15:55:13
·
answer #5
·
answered by BIF 2
·
0⤊
0⤋
5x-8y = 9
2x+3y = 16
to solve by cancelation
multiply first equation by -2 and the bottom by 5. Add vertically and the x's cancel out letting you solve for y
-10x + 16y = -18
10x + 15y = 80
31y = 62
y=2
substitute y in
2x+3(2) = 16
2x +6 = 16
2x = 10
x = 5
x =5 and y =2
2007-02-10 15:52:09
·
answer #6
·
answered by radne0 5
·
0⤊
0⤋
x=5 , y=2
2007-02-10 16:05:42
·
answer #7
·
answered by rain7maker7 2
·
0⤊
0⤋
lets say 2x=16-3y then x=16-3y/2
now put the value of x in the sec equation
5(16-3y/2) -8y =9
80-23y=18
y=62/23
put value of y in the eq. to get the value of x
2007-02-10 15:52:10
·
answer #8
·
answered by Satveer S 2
·
0⤊
1⤋
(a million, -4) 9x+2y=a million 5(9x+2y=a million) => 45x +10y = 5 2x-5y=22 2(2x-5y=22) => 4x - 10y = 40 4 upload the two... 45x +10y = 5 4x - 10y = 40 4 --------------------- 49x = 40 9 so x = a million substitute the a million interior the least confusing subject: 9x+2y=a million 9(a million) + 2y = a million 9 +2y = a million 2y = -8 y = -4
2016-11-03 03:07:52
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋